Theory of domain-wall magnetoresistance in metallic antiferromagnets - Zheng, Jun-Hui; Brataas, Arne; Klaeui, Mathias; Qaiumzadeh, Alireza (Physical Review B, 2020)
We develop a theory to compute the domain-wall magnetoresistance (DWMR) in antiferromagnetic metals with different spin structures. In the diffusive transport regime, the DWMR can be either negative or positive depending on the domain-wall orientation and spin structure. In contrast, when the transport is in the ballistic regime, the DWMR is always positive, and the magnitude depends on the width and orientation of the domain wall. Our results pave the way for using electrical measurements for probing the internal spin structure in antiferromagnetic metals.
CRIS-Team Scopus Importer:2023-03-27